From historical fiction to historiographic metafiction: Lawrence Hill’s the book of negroes as deviant Literature (2023)
Scholars have debated the classification of the African American literature as a plain historic text, which further stimulates the controversy between history and literature. It is on this presumption that this paper critically explored Lawrence Hills’ The Book of Negroes, more as a subversive text, which is constructively predisposed to certain postmodern stylistic techniques. While amplifying obtrusive matters that still affect the black race in contemporary American society, it is observed that Hill employs Historiographic Metafiction to creatively reconceptualise the narrative of African American slave history. By implication, the fictional mode in The Book of Negroes deconstructs a fixed categorisation of historical hermeneutics of African American slave narratives, as limited to the issues of slavery, captivity, racism, oppression, and so on. While using qualitative approach as methodology, Jacques Derrida’s Deconstruction served as theoretical framework, complemented by Linda Hutcheon’s conception of historiographic metafiction. As a stylistic import, this paper submits that historiographic metafiction is substantiated as a counterdiscourse against the lopsided criticism that deprecates black history and literary artistry as immaterial. With reference to its literary originality, The Book of Negroes is therefore categorised as a deviant form of black writing in contemporary times.